EKSPLORASI PENOKOHAN DAN KONFLIK INTERPERSONAL DALAM NOVEL PERANG BUBAT KARYA AAN MERDEKA PERMANA - Malik, Miftahul; Hendriansyah, Andry; Fadlan, Muhamad (Universitas Andalas, 2024)
The urgency for innovation in senior high school literature teaching materials has prompted this research. Historical novels with a psychological literary perspective are still rarely used as teaching materials. Hence, this research focuses on analyzing the characterization and conflicts in Aan Merdeka Permana's novel Perang Bubat as an alternative teaching material for senior high school literature. Employing a qualitative approach with a descriptive method, this research gathered data in the form of words and analyzed it using Sigmund Freud's psychoanalytic theory. The analyzed characters include Dyah Pitaloka, Hayam Wuruk, Gajah Mada, and Prabu Lingga Buana. The findings reveal unique character traits in the characters of Aan Merdeka Permana's novel Perang Bubat. These unique characteristics are classified into the id, ego, and superego. The research results were then transformed into senior high school literature teaching materials in the form of teaching modules and handouts. It is recommended that Aan Merdeka Permana's novel Perang Bubat be used as a teaching material for senior high school literature, particularly for grade XII, as an alternative to outdated teaching materials. The proposed teaching materials in this research are teaching modules and handouts designed to facilitate the understanding of the novel.